Limonene ozonolysis in the presence of nitric oxide: Gas-phase reaction products and yields - Ham, Jason E.; Harrison, Joel C.; Jackson, Stephen R.; Wells, J.R. (Atmospheric environment (1994), 2016)
The reaction products from limonene ozonolysis were investigated using the new carbonyl derivatization agent, O-tert-butylhydroxylamine hydrochloride (TBOX). With ozone (O3) as the limiting reagent, five carbonyl compounds were detected. The yields of the carbonyl compounds are discussed with and without the presence of a hydroxyl radical (OH) scavenger, giving insight into the influence secondary OH radicals have on limonene ozonolysis products. The observed reaction product yields for limonaketone (LimaKet), 7-hydroxyl-6-oxo-3-(prop-1-en-2-yl)heptanal (7H6O), and 2-acetyl-5-oxohexanal (2A5O) were unchanged suggesting OH generated by the limonene + O3 reaction does not contribute to their formation. The molar yields of 3-isopropenyl-6-oxo-heptanal (IPOH) and 3-acetyl-6-oxoheptanal (3A6O) decreased by 68% and >95%; respectively, when OH was removed. This suggests that OH radicals significantly impact the formation of these products. Nitric oxide (NO) did not significantly affect the molar yields of limonaketone or IPOH. However, NO (20 ppb) considerably decreased the molar reaction product yields of 7H6O (62%), 2A5O (63%), and 3A6O (47%), suggesting NO reacted with peroxyl intermediates, generated during limonene ozonolysis, to form other carbonyls (not detected) or organic nitrates. These studies give insight into the transformation of limonene and its reaction products that can lead to indoor exposures. •Aqueous collection and derivatization of gas-phase limonene ozonolysis products.•Multi-functional gas-phase carbonyls detected from limonene ozonolysis.•Hydroxyl radical's and nitric oxide's influence on reaction product formation.